Tipologi Motivasi Perubahan Tutupan Lahan Sub DAS Molamahu - Dicky Artha; Irwan Bempah; Wawan K. Tolinggi (Transbahasa, 2026)
Land cover change in watersheds is not merely a biophysical or technical process, but a socially negotiated outcome shaped by market dynamics, policy frameworks, and power relations. This conceptual study synthesizes existing literature and policy documents without conducting primary fieldwork; it relies entirely on secondary data to construct a motivational typology. This study aims to analyze community motivations underlying land cover change using an environmental sociology perspective, with the Molamahu sub-watershed in Gorontalo as a case study. The research adopts a qualitative case study design based on secondary data, including policy documents, scientific publications, and thematic reports on dryland livelihoods and socio-cultural dynamics. Data were analyzed thematically by integrating three analytical frameworks, namely the distinction between proximate and underlying drivers of land change, structuration theory to interpret agency and structure relations, and the livelihoods approach to examine household strategies. The findings reveal six main motivational pathways, namely livelihood security, economic accumulation, tenure reinforcement, social network influence, policy incentives, and ecological rationality based on risk perception. These pathways interact dynamically and often ambivalently, simultaneously encouraging agricultural expansion and enabling conservation practices such as agroforestry when supported by appropriate incentives and institutional arrangements. This study proposes a typology of motivations and highlights policy implications that frame watershed management as an arena of environmental justice, emphasizing equitable cost-benefit distribution, strengthened local institutions, and secure land tenure.